EFFECTIVENESS AND CONTRIBUTION OF PUBLIC SERVICE RETRIBUTIONS TO REGIONAL REVENUE IN JOMBANG - Hadi Sucipto (Eksis: Jurnal Riset Ekonomi dan Bisnis, 2022)
This study aims to determine the Effectiveness and Contribution of public service fees to receiving local revenue in Jombang Regency. This study uses a quantitative approach. The data used is secondary data originating from reports on the realization of the Jombang Regency regional revenue and expenditure budget for 2018-2020. The results showed that the level of Effectiveness of general service fees for the 2018 period was quite effective, with a percentage of 87%; in 2019, it was in the effective category with a percentage of 99%; in 2020, it was in the category quite effective with a percentage of 80%. Meanwhile, the Contribution of public service fees to local revenue receipts for 2018 to 2020 is very lacking, with the percentage in 2018 at 8%, in 2019 at 6%, and in 2020 at 3%. Keywords: Effectiveness, Contribution, Public Service Retribution, Regional Original Revenue, Jombang